Bifunctional Al2O3 Interlayer Leads to Enhanced Open‐Circuit Voltage for Hole‐Conductor‐Free Carbon‐Based Perovskite Solar Cells. Issue 5 (22nd February 2018) - Xiong, Yuli; Zhu, Xiaotong; Mei, Anyi; Qin, Fei; Liu, Shuang; Zhang, Shujing; Jiang, Youyu; Zhou, Yinhua; Han, Hongwei
Abstract : Hole‐conductor‐free carbon‐based perovskite solar cell (C‐PSC) is respected for their low cost and super stability. However, its absolut e efficiency is hampered by the relatively low open‐circuit voltage ( V oc ) due to the higher recombination losses than device with hole conductors. Herein, we develop a novel architecture to improve the V oc through simple incorporation of an Al2 O3 interlayer. We find that this Al2 O3 interlayer not only serves as an excellent insulating layer to separate cathode and anode but also modifies the interface between the electron transport material (ETM) and perovskite, and thus effectively retards the recombination at ETM/perovskite and perovskite/counter electrode interfaces simultaneously. Significantly, the average V oc of hole‐conductor‐free C‐PSC upon the adoption of Al2 O3 interlayer is increased from 836 to 942 mV. This novel architecture design combine the surface modification and spacer tuning technologies through a facile step, which makes an important step toward obtaining high efficient hole‐conductor‐free C‐PSC. Abstract : This Al2 O3 interlayer acts as an excellent insulating layer and interface decorator for electron transport material (ETM), which effectively reduces the recombination at ETM/perovskite and perovskite/counter electrode interfaces simultaneously, thus leading to an enhanced open‐circuit voltage for hole‐conductor‐free carbon‐based perovskite solar cell.